Movies and Acceptance and Commitment Therapy: Intervention from “Frozen” and “Partly Cloudy” (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
This paper presents part of the analysis developed in the research project “Cinema and Acceptance and Commitment Therapy (ACT): contributions to therapeutic interventions”. The project aimed to analyze six films, seeking to specify the aspects that contribute to clinical interventions with emphasis on ACT relating them to therapeutic situations and using the findings to teach the basics and how to intervene on this proposal. After the selection of films, the scenes were described and discussed using the theory as a basis, emphasizing its contribution to clinical interventions. We found that the selected films discussed issues worked out by ACT (such as merger and control of the causes), showed that the avoidance pattern of private/covert aversive events widens the suffering and distance values, and illustrated the stages through which customers need to go to achieve progress in therapy. For this work, the analysis of “Frozen” and “Partly Cloudy” will be described.
Keywords: acceptance and commitment therapy; behavior analysis; films